2020
DOI: 10.1093/geroni/igaa029
|View full text |Cite
|
Sign up to set email alerts
|

Does Visual Speed of Processing Training Improve Health-Related Quality of Life in Assisted and Independent Living Communities?: A Randomized Controlled Trial

Abstract: Background and Objectives Visual speed of processing training had clinically and statistically significant beneficial effects on health-related quality of life among 2,802 healthy community-dwelling adults 65-94 years old at two and five years post-training in the Advanced Cognitive Training for Independent and Vital Elderly randomized controlled trial. We examined whether that effect would be found among older adults in assisted and independent living communities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…While cognitive training app games have been shown to improve memory in older people with mild cognitive impairment 63 , further studies are needed to determine if technologies, such as apps, can decrease dementia risk in healthy subjects or slow down the progression of the disease in patients suffering from cognitive impairment and if there is a transfer to the activities of daily living. We can, also, speculate that since psychomotor slowing associated with aging has an important negative effect on multi-tasking activities of daily living, improving the processing speed could have a positive effect on the quality of life of the participants 64 .…”
Section: Discussionmentioning
confidence: 96%
“…While cognitive training app games have been shown to improve memory in older people with mild cognitive impairment 63 , further studies are needed to determine if technologies, such as apps, can decrease dementia risk in healthy subjects or slow down the progression of the disease in patients suffering from cognitive impairment and if there is a transfer to the activities of daily living. We can, also, speculate that since psychomotor slowing associated with aging has an important negative effect on multi-tasking activities of daily living, improving the processing speed could have a positive effect on the quality of life of the participants 64 .…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, as all trained groups suggest an apparent adverse effect of training on mortality, this is curious and remains unexplained. It is possible that low-educated individuals found the training more stress-inducing, leading to negative psychological (e.g., negative self-identity perceptions) and physiological (e.g., elevated cortisol levels) responses associated with increased mortality (e.g., [Wolinsky et al, 2020]). However, since we did not measure these variables, we can only speculate about the etiologic mechanisms underlying the education-training interactions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wolinsky et al (2013) reported that 28.3% of their middle-and old-aged adults (> 50 years) who trained at home performed less than 1 h (out of 10 h) of training in a visual speed task. In a follow-up study, Wolinsky et al (2020) found also a great variety of adherence to a visual processing speed training a community-based sample of older adults (> 55 years). Chan and colleagues (2016) conducted a field training study targeting older adults (60-90 years) in a community setting which included homework as well as group training for an extensive time (> 150 h).…”
Section: Adherence To a Home-based Task-switching Training In Middle-aged Caregiversmentioning
confidence: 95%